Executing Quality Management Tools to Enhance Customer’s Journey at a Clothes Laundry Firm - Mohammed Alshahrani; Mahmoud Alabdali; Wafa Zaid; Rola Mohammod; Khalid S. M. Husain (European Scientific Journal, ESJ, 2023)
Purpose: This paper focuses on assessing and enhancing the customer’s journey at a laundry company in Saudi Arabia. This begins from the moment the customer arrives at the car park, including the process of receiving the services and subsequently making payment. Design, Methodology, Approach: A mixed-method approach was employed and qualitative data were gathered from focus group interviews and individual interviews. Quantitative data were gathered via the survey. Quality Management Tools were used to develop the action plan and offer conclusions and recommendations that would enhance the customer’s journey and improve satisfaction. Findings: Issues relating to service quality are categorized into five types: promotions, human resources, services, detergent products, and facilities. House of Quality represents the highest 15 prioritized solutions. These recommended solutions' relative weights range between 4 to 9%. The use of these tools highlights areas for improvement and the root causes of each issue. The voice of the customer and the voice of the employees are key sources to obtain valuable input. This research proffers step-by-step practical guideline for service organizations on how they can apply the quality management tools in their business, which will help them identify issues and continue improving. Its implications to academia merge the ServQual theory and QM in customer services and satisfactions. Originality/Value: This study will add value to the literature since there are limited studies employing the seven Quality Management Tools to enhance customer satisfaction and improve their journey. The Saudi laundry market specifically has a dearth of this type of study. The leadership of an organisation in the laundry sector is established through the implementation of tailored quality solutions, the prioritisation of customer satisfaction, and the enhancement of operational efficiency.